IMPLEMENTASI PRINSIP HUKUM EKONOMI SYARIAH DALAM SEWA MENYEWA LOS PASAR - Haruna R, Nur Nilam Sari; Darmawangsa, Andi; Lawang, Hasanna; Abu Baedah, Said Syafuddin; Subaedah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the practice of leasing market stalls and analyze the implementation of Islamic economic law principles in these practices at Terong Market, Makassar. The background of this study is based on the continued discovery of rental contracts conducted orally without written records, thus potentially creating legal uncertainty and non-compliance with Islamic economic law principles, particularly regarding contract clarity and transparency. This study uses a qualitative method with a field research approach. Data collection techniques are carried out through observation, interviews, and documentation. Informants in this study consist of market managers, traders as stall tenants, and other related parties. The data obtained are analyzed descriptively qualitatively with reference to the theory of ijarah and the principles of Islamic economic law. The results of the study indicate that the practice of leasing stalls at Terong Market, Makassar is carried out through two mechanisms: officially through market managers with written contracts, and informally through third parties which are generally carried out orally. In practice, some principles of Islamic economic law have been met, such as the principles of justice (al-'adalah), willingness (al-ridha), freedom of contract (al-hurriyah), and equality (al-musawah). However, their implementation is not yet fully optimal, particularly in the aspects of contract recording (al-kitabah) and information transparency. This situation has the potential to give rise to elements of gharar (unlawful) that can affect legal certainty and fairness in transactions. Therefore, improvements are needed through the implementation of written contracts, increased transparency, and education for market players so that leasing practices comply with the principles of Islamic economic law.